Building capacity on Berlin's urban dancefloor: How club culture shapes sustainable urban transformation while negotiating contested space - Klibingat,Nina (Master Thesis Series in Environmental Studies and Sustainability Science, 2026)
Cultural spaces remain underexplored in sustainable urban transformation research. Berlin’s club culture is entangled with contested urban spaces and currently threatened by acute urbanization pressures. This qualitative case study draws on six expert interviews and participant observation to explore club culture’s role in Berlin’s sustainability transformation, interpreted through cultural sustainability (Soini & Dessein, 2016) and urban transformative capacity (Hofstad et al., 2026) frameworks. It reveals that club culture builds primarily experimental and ideational capacity through sustaining itself, with civil society intermediaries as drivers. Actors negotiate plural and contested understandings of sustainability, shaped by institutional context. Space emerges as central contested resource and material precondition for building transformative capacity, undertheorized by the UTC framework. The key challenge is not mere preservation but protecting the conditions of affordable space, governance autonomy, and temporary use rights to allow club culture and Berlin to transform together.
Keywords: Sustainability Science; Cultural Sustainability; Urban Transformative Capacity; Club Culture; Berlin